Whither Cognitive Bias Modification Research? Commentary on the Special Section Articles. - MacLeod, Colin; Koster, Ernst H. W.; Fox, Elaine (Journal of Abnormal Psychology, 2009)
This commentary reviews key theoretical, methodological, and clinical issues raised by recent research on cognitive bias modification (CBM). The authors identify the major ways in which the new work reported within this special section extends earlier CBM research. In particular, they note that it considers a wider range of participants, includes a greater diversity of symptoms measures, and targets for change a broader array of processing biases than previously has been the case. Furthermore, they point out that the present work develops and employs a more diverse arsenal of bias modification procedures, in some cases delivered across extended periods of time within naturalistic settings. They also draw attention to methodological limitations associated with the current studies, offering recommendations concerning how future CBM research might profitably build upon these exciting new directions while overcoming such limitations. Finally, they evaluate the theoretical and applied implications of the reported findings, discussing their capacity to illuminate the causal contributions made by cognitive bias to emotional vulnerability and their promise concerning the potential therapeutic value of CBM as a clinical tool. Reprinted by permission of the publisher.